A multi-criteria decision support tool for selecting circular economy business models - Somorin, Tosin; Gebrezgabher, Solomie A.; Ghosh, Surajit; Taron, Avinandan; Bodach, Susanne (CGIAR Initiative on Nature-Positive Solutions; CGIAR Initiative on Resilient Cities, 2023)
Waste management has become a pivotal public health and environmental question, particularly in developing nations, due to rapid industrialization, population growth, and inadequate policy. To foster a long-term pattern of progress, global trends are encouraging governments, policymakers, and international organizations to explore pathways for transitioning from linear to circular economy business models. Resource Recovery and Reuse (RRR) offers viable pathways with multiple value propositions beyond environmental benefits. However, the decision-making processes involved in the shaping and selection of business models often require weighing costs and benefits and making trade-offs among alternatives and competing priorities. Some costs and benefits are clearly identifiable and can be numerically expressed, yet many others cannot be readily determined. This technical report presents the conceptual framework underlying a multi-criteria-based decision support tool tailored to enable decisionmakers and practitioners to select appropriate and sustainable CE business models in the RRR context with positive social, economic, and environmental outcomes.